2021
DOI: 10.3390/ijerph182010929
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Symptomatic COVID-19 in Phuentsholing Municipality, Bhutan

Abstract: COVID-19 is a disease that is caused by a highly transmissible and pathogenic novel coronavirus: severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). All of the COVID-19 positive cases in Bhutanese travellers returning via the Phuentsholing point of entry, the local population, and Indian nationals were isolated in the Phuentsholing COVID-19 isolation ward, Bhutan. This study aimed to identify the risk factors for developing symptoms among COVID-19 positive patients in this ward. A retrospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
3
4
0
2
Order By: Relevance
“…In this study, the common symptoms were fever, cough, and headache. These findings were in agreement with other studies, where commonly reported symptoms were fever, sore throat, headache, cough, and myalgia ( 19 , 24 , 28 ). COVID-19 tends to be more severe in adults and the elderly with devastating health outcomes in immunocompromised and patients with co-morbidities ( 26 , 29 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, the common symptoms were fever, cough, and headache. These findings were in agreement with other studies, where commonly reported symptoms were fever, sore throat, headache, cough, and myalgia ( 19 , 24 , 28 ). COVID-19 tends to be more severe in adults and the elderly with devastating health outcomes in immunocompromised and patients with co-morbidities ( 26 , 29 ).…”
Section: Discussionsupporting
confidence: 93%
“…A study on the work-related COVID-19 in six Asian countries including Hong Kong, Japan, Singapore, Taiwan, Thailand, and Vietnam reported “drivers and transport workers” contributed upto 18% of the COVID-19 burden ( 37 ). A similar finding of a higher risk of reporting symptoms among people working in the transportation services was also reported in Phuntsholing Municipality in Bhutan ( 24 ). Loaders tranship the goods entering Bhutan, from Indian vehicles to Bhutanese vehicles.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The coronavirus disease 2019 (COVID-19) in Bhutan was first confirmed on 5 March 2019, in a 76-year-old tourist [ 2 ]. Subsequently, there were sporadic cases and localized outbreaks in different parts of the country [ 3 ]. As of 15 September 2021, there were 2,596 confirmed cases and three deaths in the country (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A large volunteer workforce, known locally as Desuups ( www.desuung.org.bt ), came forward to facilitate the organization of vaccination rounds and other activities to control COVID-19 [ 3 ]. Founded by the Fifth King, Desuup trainees undergo a value-based personal development program to encourage volunteerism for community services and play an active role in building the nation.…”
Section: Introductionmentioning
confidence: 99%